Acceptability of opt‐out consent in a hospital patient population. Issue 1 (3rd January 2018) - Boulos, Daniel; Morand, Eric; Foo, Michelle; Trivedi, Janki Dhaval; Lai, Ruth; Huntersmith, Rachel; Zhang, Karen; Stark, Claire Brigid; Le, Suong
Abstract: Research has been slow to leverage digitalised medical records as a data resource. Our study assessed patient acceptability of opt‐out consent for secondary use of digital patient data. A questionnaire was distributed to patients in multiple languages and with an interpreter. Of 919 completed surveys, 33% were of non‐English speaking background, 15% self‐reported cognitive impairment and 3% were refugees. Opt‐out consent was accepted in this diverse population; 87% of participants approved, or were indifferent to opt‐out consent. Gender, employment and cognition status were not significant determinants of acceptability.